Genotypic and Phenotypic Characterization of Clinical Escherichia coli Sequence Type 405 Carrying IncN2 Plasmid Harboring blaNDM-1 - Yingying Hao; Chunhong Shao; Xu Geng; Yuanyuan Bai; Yan Jin; Zhiming Lu (Frontiers in Microbiology, 2019)
We report a blaNDM-carrying ST405 Escherichia coli recovered from the abdominal fluid of a patient in Shandong, China. This strain belonged to the high-risk phylogenetic group D and carried the virulence genes, papG II, papG III, papC, and iroN. In addition to blaNDM-1, this isolate carried the quinolone resistance gene acc(6′)-Ib and extended-spectrum β-lactamase (ESBL) genes blaCTX-M-15 and blaCTX-M-14. blaNDM-1 was located on a 41 Kb IncN2 self-transmissible plasmid. The IncN2 plasmid named as pJN24NDM1 was fully sequenced and analyzed. Genome comparative analysis showed that IncN2 plasmids harboring carbapenem-resistance genes possessed conserved backbones and variable accessory regions. Phylogenetic analysis of 87 IncN plasmids based on orthologous genes indicated that 9 IncN2 plasmids fell into one phylogenetic clade, while 4 IncN3 plasmids were in two phylogenetic clades of the 74 IncN1 plasmids. The presence of IncN2 plasmids harboring blaNDM in the high-risk clone ST405 E. coli raises serious concerns for its potential of dissemination.